Analysis and optimisation of disc brake calipers - Sergent, Nicolas (Cranfield University, 2010)
Disc brake calipers are subjected to complex mechanical loading and interaction of individual components in a typical brake assembly makes design improvement very challenging. To analyse caliper behaviour, complex Finite Element models were created and successfully validated using a variety of experimental techniques, including exceptionally suitable Digital Image Correlation. A novel methodology to optimise caliper design was developed, using non-linear contact Finite Element Analysis and topology optimisation, to generate lightweight, high performance brake calipers. The method was used on a Formula 1 brake assembly and significant improvement in structural design was achieved, with the new caliper being lighter and stiffer than the original. The same approach was used on more conventional 4 pistons calipers using various boundary conditions with particular focus on mass reduction and considerably lighter designs were achieved. The influence of specific features of the optimised calipers on the structural performance was also successfully investigated.
Keywords: Finite Element Analysis; pressure distribution; digital image correlation; topology; optimisation